Challenges and opportunities for improving eco-efficiency of tropical forage-based systems to mitigate greenhouse gas emissions - Peters, Michael; Herrero, Mario; Fisher, M.; Erb, Karlheinz; Rao, Idupulapati M.; Subbaraoa, Guntur V.; Castro, A.; Arango, Jacobo; Chara, J.; Murgueitio, E.; Hoek, Rein van der; Läderach, Peter R.D.; et al. (2013)
Forage-based livestock production plays a key role in national and regional economies, for food security and poverty alleviation, but is considered a major contributor to agricultural GHG emissions. While demand for livestock products is predicted to increase, there is political and societal pressure both to reduce environmental impacts and to convert some of the pasture area to alternative uses, such as crop production and environmental conservation. Thus, it is essential to develop approaches for sustainable intensification of livestock systems to mitigate GHG emissions, addressing biophysical, socio-economic and policy challenges. This paper highlights the potential of improved tropical forages, linked with policy incentives, to enhance livestock production, while reducing its environmental footprint. Emphasis is on crop-livestock systems. We give examples for sustainable intensification to mitigate GHG emissions, based on improved forages in Brazil and Colombia, and suggest future perspectives.